Love is strange [videorecording (DVD)] - Sachs, Ira; Lithgow, John, 1945-; Molina, Alfred, 1953-; Tomei, Marisa; Burrows, Darren E., 1966-; Jackson, Cheyenne
After nearly four decades together, Ben and George finally tie the knot in an idyllic wedding ceremony in lower Manhattan. But when George loses his job, the couple must sell their apartment and temporarily live apart until they can find an affordable new home. George moves in with two cops who live down stairs while Ben lands in Brooklyn with his nephew, his wife, and their teenage son. While struggling with the pain of separation, they are challenged by the tensions and capricious family dynamics of their new living arrangements.